Reducing Psychosocial Risk Factors and Improving Employee Well-Being in Emergency Departments: A Realist Evaluation - de Wijn, Anne Nathal; van der Doef, Margot Petra (Frontiers in Psychology, 2022)
This study reports the findings of a 2.5 year intervention project to reduce psychosocial risks and increase employee well-being in 15 emergency departments in the Netherlands. The project uses the psychosocial risk management approach `PRIMA` which includes cycles of risk assessment, designing and implementing changes, evaluating changes and adapting the approach if necessary. In addition, principles of participative action research were used to empower the departments in designing and implementing their own actions during the project. Next to determining overall effects, the study aims to assess potential moderators including the level of intervening (organization-directed or multilevel), process variables (the number and fit of actions to risk factors, communication and employee participation) and partaking in a Psychosocial Safety Climate intervention offered during the second half of the project. The results of linear mixed-model analyses showed that all job factors improved with the exception of autonomy, which did increase halfway the project but not when considering the entire timeframe. In addition, work engagement decreased and symptoms of burnout remained stable. Emergency departments that implemented more fitting actions, communicated better and involved their employees more in the process, had more favorable changes in job factors and more stable well-being. More activity (based on the number of actions implemented) and a multilevel approach regarding stress management did not lead to greater improvements. The Psychosocial Safety Climate intervention was effective in improving Psychosocial Safety Climate, but a longer follow-up period seems required to evaluate its effect on job factors and well-being. Overall, the project resulted in positive changes in most job factors, and its findings emphasize the importance of process variables in stress management interventions. Longer follow-up and higher quality multilevel interventions (including professional support for employees with stress-related complaints) seem essential to also improve well-being.